1999
DOI: 10.1016/s0014-5793(99)00357-9
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic stretch induces both apoptosis and secretion in rat alveolar type II cells

Abstract: We examined the effects of short-term cyclic stretch on both phosphatidylcholine (PC) secretion and apoptosis in primary cultures of rat alveolar type II cells. A 22% cyclic stretch (3 cycles/min) was applied to type II cells cultured on silastic membranes using a Flexercell strain unit. This induced, after a lag period of about 1 h, a small, but significant release of [ Q H]PC from prelabelled cells. In addition, stretch increased nuclear condensation, the generation of oligosomal DNA fragments and the activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 29 publications
6
51
1
2
Order By: Relevance
“…A role for stretch-induced apoptosis in lung development was first suggested by De Paepe et al (11), who showed that depletion of AEC2 after tracheal ligation in fetal rabbits was at least in part due to an increase in apoptosis. Similarly, 20% radial elongation stimulated apoptotic activity in primary adult AEC2 (35). However, these studies performed tissue distension under conditions greater than those considered "physiologic" during gestation.…”
Section: Biophysical Stimuli Of Apoptosismentioning
confidence: 99%
“…A role for stretch-induced apoptosis in lung development was first suggested by De Paepe et al (11), who showed that depletion of AEC2 after tracheal ligation in fetal rabbits was at least in part due to an increase in apoptosis. Similarly, 20% radial elongation stimulated apoptotic activity in primary adult AEC2 (35). However, these studies performed tissue distension under conditions greater than those considered "physiologic" during gestation.…”
Section: Biophysical Stimuli Of Apoptosismentioning
confidence: 99%
“…Mechanical stresses have been shown to play an important role in regulating various functions of pulmonary epithelial cells such as growth (1)(2)(3), apoptosis (4-7), migration (8,9), surfactant metabolism (1,6,(10)(11)(12), synthesis of extracellular matrix proteins (11,13), and transport of fluids and ions (12,14,15). Disruption of the local mechanical environment of the pulmonary epithelium often elicits abnormal cellular responses and can contribute to the pathogenesis and progression of various respiratory diseases (4,5,(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Mechanical distention of isolated and cultivated fetal alveolar cells promotes their differentiation to AT I cells whereas that lack of distention promotes the differentiation to ATII cells (Edwards, 2001). Besides affecting cell differentiation and lung development there is also evidence for the contribution of physical stress as a factor that mediates production and secretion of surfactant proteins by ATII cells (Edwards et al, 1999) as well as by cultured H441 cells (Sanchez-Esteban et al, 1998). There is also evidence that mechanical forces induce apoptosis in ATII cells (Edwards et al, 1999;Hammerschmidt et al, 2007).…”
Section: Strain Is Crucial For Several Functions Of Epithelial Cellsmentioning
confidence: 99%